Generation of electric solitary structures electron holes by nonlinear low-frequency waves - Lakhina, G.S.; Tsurutani, B.T.; Pickett, J.S. (My University, 2005)
High resolution electric and magnetic wave data, obtained by Polar during its passage through the polar cap/cusp boundary layer, show large amplitude low-frequency electromagnetic waves and electric bipolar pulses electron holes. It is proposed that nonlinear low-frequency waves, consisting of Alfven and/or proton cyclotron waves, can drive high-frequency electrostatic modes which saturate by trapping electrons, thereby leading to the generation of electron holes. The free energy sources for these electrostatic instabilities are the parallel currents, which are produced due to relative motion of electrons and ions in the presence of large amplitude low-frequency waves.
Keywords: Electric solitary; Electron holes; Magnetic waves; Electromagnetic waves; Low-frequency waves; Alfven waves